مدى قدرة محافظ الحسابات على المراجعة في ظل نظم المعلومات الإلكترونية – دراسة تحليلية لآراء عينة من محافظي الحسابات في الجزائر- - زين, عيسى; أحمد قايد, نور الدين (جامعة الوادي - University of Eloued, 2017)
تهدف هذه الدراسة إلى التعرف على مدى قدرة محافظ الحسابات الجزائري على أداء مهامه في ظل نظم المعلومات الإلكترونية، وتبيان مشاكل المراجعة في ظل هذه النظم بغية المساهمة في تحسين خدمات مكاتب المراجعة بالجزائر، وهذا من خلال دراسة تحليلية للآراء عينة من محافظي الحسابات الجزائريين، وأجريت باستخدام استبيان تم تصميمه بالاعتماد على الدراسات السابقة والدراسة النظرية. وقد خلصت هذه الدراسة إلى أن محافظ الحسابات بالجزائر وفريقه لديه الكفاءة العلمية والعملية التي تسمح لهم بمراجعة مؤسسات تستخدم نظم المعلومات الإلكترونية إلا أنه على الرغم من ذلك يوجد أمام محافظي الحسابات بالجزائر مشاكل أثناء مراجعة حسابات المؤسسات المستخدم لنظم المعلومات الإلكترونية. The aim of this study is to identify the extent of Algerian external auditors to perform the tasks under the electronic information systems, and to explain the audit problems under these systems in order to contribute to the improvement of the services of the auditing offices in Algeria, through an analytical study of the views of a sample of the Algerian accountants and conducted using a questionnaire that was designed based on previous studies and theoretical study. The study concluded that the external auditors in Algeria and his team has the scientific and practical competence to auditing institutions using electronic information systems, However, in spite of this, the external auditors in Algeria have problems during auditing the institutions used for electronic information systems.
مقال
Keywords: محافظ الحسابات، نظم المعلومات الإلكترونية، مراجعة الحسابات، تكنولوجيا المعلومات; auditor, electronic information systems, auditing, Information